[Neuro]-therapy: Alternative Intervention for Memory Disorder - ChePa, Noraziah; Yusoff, Nooraini; Wan Yahaya, Wan Ahmad Jaafar; Ishak, Rusdi; Sie-Yi, Laura Lim (Multidisciplinary Applied Research and Innovation, 2021)
Concerns on finding appropriate and the most efficient way of treating elderly suffering with memory disorder diseases like Dementia and Alzheimer have been a growing issue of discussions over a decade. Current pharmacological treatment is expensive and has its drug side effects. Therefore, alternative solutions are needed in giving harmless and more leisure treatment to the patients. Throughout the past years, various researchers and scientists have come up with various alternative treatments, including the ones in helping to simulate the brain and one of them is by using games. Although various games have been created for elderly, not all games are suitable to be used in memory treatment. Most of the games were not developed specifically for memory disorder patients. They are not created to suit these audiences because there are no known guidelines to help in creating a proper game. This project introduced [Neuro]-therapy, a game designed and developed based on specific criteria which comprises of 20 criteria of psychotherapy-intervention for memory disorder patients. The criteria are categorized into four main categories; gameplay, device, interface and game features. The game is available in Android environment and has been successfully evaluated through both verification and validation involving 55 respondents among elderly. Findings show that the proposed [Neuro]-therapy game is usable among elderly for psychotherapy purposes. Series of psychotherapy experiments have been conducted during the period of Movement Control Order (MCO). [Neuro]-therapy has become an alternative to elderly who are restricted from outside world during MCO. The game is proven to give benefits to many parties; the scholars, practitioners, caretakers, and patients. It is hope that it will give directions to developers on developing more games for memory disorder patients towards improving the quality of life among the elderly with memory disorder issues.